Studi Etnobotani Minuman Pokak Di Desa Clarak Kabupaten Probolinggo Sebagai Potensi Wisata Kuliner - Fitriyah Heni Dwi N; Mala Herfian; Mohammad Malik Trias; M. Cholid Wahyudi; Rafiatul Hasanah (-)
Wedang Pokak or Pokak syrup is a traditional drink. This drink is made from a mixture of ginger, cinnamon, lime leaves, lemongrass, sugar, and other spices. The people of Probolinggo usually serve this drink during Eid. Pokak syrup is believed to be useful for warming the body, eliminating body odor, and containing natural antioxidants. This ethnographic research was conducted with data collection techniques in interviews and questionnaires as secondary data. Interviews were conducted by purposive sampling, namely producers and consumers of Pokak syrup. The data collected were analyzed using descriptive techniques. The results showed that from 7 types of plants as the main ingredients of Pokak syrup, it could be obtained easily around the community yards of Clarak Village. The most widely used plant organs in making Pokak syrups are the stems and leaves. The materials used belong to different families, including spices, and are angiosperms division.